Band Tunable CdSe Quantum Dot-Doped Metals for Quantum Dot-Sensitized Solar Cell Application - Dang Huu Phuc; Ha Thanh Tung (International Journal of Photoenergy)
Quantum dots are drawing great attention as a material for the next-generation solar cells because of the high absorption coefficient, tunable band gap, and multiple exciton generation effect. In search of the viable way to enhance the power conversion efficiency of quantum dot-sensitized solar cells, we have succeeded in preparing the quantum dot solar cells with high efficiency based on CdSe:X (Mn2+ or Cu2+) nanocrystal by successive ionic layer absorption and reaction. The morphological observation and crystalline structure of photoanode were characterized by field-emission scanning electron microscopy, X-ray diffraction, and the EDX spectra. In addition, the electrochemical performance of photoelectrode was studied by the electrochemical impedance spectra. As a result, we have succeeded in designing QDSSCs with a high efficiency of 4.3%. Moreover, the optical properties, the direct optical energy gap, and both the conduction band and the valence band levels of the compositional CdSe:X were estimated by the theory of Tauc and discussed details. This theory is useful for us to understand the alignment energy structure of the compositions in electrodes, in particular, the conduction band and valence band levels of CdSe:X nanoparticles.